Can Increased Intra-Continental Trade Partnerships Diversify Export Baskets in Africa? - Sibusiswe Mchani; Andrew Phiri (Managing Global Transitions)
The study investigates the potential of the African Continental Free Trade Area (AfCFTA) agreement in fostering diversified export baskets through increased intra-continental trade partnerships. It aims to evaluate how these trade partnership influence export diversification within Africa. Using network analysis, it develops three indices to measure the degree, closeness, and prestige of trading partners across 54 African countries from 2000 to 2020. These indices, along with traditional estimators, reveal two key findings. Firstly, the quality of trade partnerships, focusing on ‘who’ a country trades with, holds more significance than quantity. Secondly, there is a geographical imbalance, where the effect of trade partnerships turns negative for countries with higher product diversification. In conclusion, while intra-continental trade diversification shows promise, more advanced African nations may experience diminishing returns, suggesting a need for expanding trade networks beyond the continent for sustained export diversification.